ASPECTS OF LEADERSHIP WITHIN THE JAVANESE WORLDVIEW - John Carter Mulkey; Hery Susanto (SAGACITY : Journal of Theology and Christian Education, 2022)
In all cultures people begin to develop the basic assumptions and values that make up their worldview very early in life, usually taught within the family environment. The Javanese are no different. They are taught (sometimes through parables and proverbs, sometimes through the wayang) what it means to have respect for others, especially those in positions of authority. They are taught the importance of living in harmony with their fellow man. They have learned that their leaders have an inner supernatural power that is God given, and therefore should not be questioned, especially as long as the leader is taking good care of them. The leader can also learn from the wayang character Semar, who though worthy of honor because of his position was willing to “humble himself” taking on the role of a servant for the sake of those he was serving. Within this article we look at how the study of Leadership Emergence Theory can enhance the lives and ministries of Javanese leaders.